2021
DOI: 10.1016/j.vaa.2021.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sedative effects of xylazine alone or combined with levomethadone or ketamine in calves prior to disbudding

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Reedman et al (2021) [36] demonstrated that calves disbudded under sedation with xylazine in addition to local anaesthetic and parenterally administered NSAID had a higher rate of play behaviour 24 h post disbudding compared to their non-sedated counterparts. Other studies have been completed to investigate novel and xylazine-sparing drug protocols, including the administration of levomethadone and ketamine [37], although the impacts on pain relief and behaviour are unknown. Negative control trials, where possible, will help to establish the direct impact of NSAIDs as opposed to comparing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Reedman et al (2021) [36] demonstrated that calves disbudded under sedation with xylazine in addition to local anaesthetic and parenterally administered NSAID had a higher rate of play behaviour 24 h post disbudding compared to their non-sedated counterparts. Other studies have been completed to investigate novel and xylazine-sparing drug protocols, including the administration of levomethadone and ketamine [37], although the impacts on pain relief and behaviour are unknown. Negative control trials, where possible, will help to establish the direct impact of NSAIDs as opposed to comparing treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, xylazine is allowed for use under the USDA-NOP but must be used by or under the direction of a veterinarian (The National List of Allowed and Prohibited Substances (§205.603) [ 59 ]. In Finland, Adam et al [ 61 ] reported that a low dose of xylazine allowed for sufficient sedation as a local anesthetic for disbudding in Finnish Ayrshire calves. However, xylazine does have a side effect of decreasing core body temperature after injection for dairy calves that were disbudded [ 62 ].…”
Section: Pain Management For Disbuddingmentioning
confidence: 99%